2010
DOI: 10.1002/anie.201002802
|View full text |Cite
|
Sign up to set email alerts
|

Glycosidase Inhibition with Fullerene Iminosugar Balls: A Dramatic Multivalent Effect

Abstract: Superball! A dodecavalent iminosugar derivative with a fullerene core (see picture) shows a binding enhancement of up to three orders of magnitude over the corresponding monovalent ligand in glycosidase inhibition assays. This is the first evidence of a significant multivalent effect in glycosidase inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 182 publications
(127 citation statements)
references
References 40 publications
3
124
0
Order By: Relevance
“…Apart from their unique architecture, hexakis adducts derived from the functionalization of the six e double bonds of C 60 are very attractive structures in the synthesis of functional fullerene materials. [45][46][47][48][49][50] The results of the present study lead to the conclusion that the [4+2] cycloaddition of orthoquinodimethanes with the C 60 is a kinetically controlled reaction. The in situ thermal generation of ortho-quinodimethanes from the corresponding 1,2-bis(bromomethyl)benzene precursors requires high temperatures (110 o C) and is followed by the fast, irreversible [4+2] cycloaddition reaction with C 60 to afford thermally stable products.…”
Section: Scheme 6 Synthesis Of Macrocyclic Tether 21supporting
confidence: 58%
“…Apart from their unique architecture, hexakis adducts derived from the functionalization of the six e double bonds of C 60 are very attractive structures in the synthesis of functional fullerene materials. [45][46][47][48][49][50] The results of the present study lead to the conclusion that the [4+2] cycloaddition of orthoquinodimethanes with the C 60 is a kinetically controlled reaction. The in situ thermal generation of ortho-quinodimethanes from the corresponding 1,2-bis(bromomethyl)benzene precursors requires high temperatures (110 o C) and is followed by the fast, irreversible [4+2] cycloaddition reaction with C 60 to afford thermally stable products.…”
Section: Scheme 6 Synthesis Of Macrocyclic Tether 21supporting
confidence: 58%
“…[36] More recently, Compain and Nierengarten described a fullerene iminosugar ball that was assayed against a range of glycosidases and displayed a relative inhibition potency of 179 compared with the monomeric structure, also against Jack bean a-mannosidase. [9] These literature data clearly indicate that all enzymes are not prone to multivalent inhibition and that the nature of both the central core structure and the spacer unit tethering the inhibitory monomers play critical roles in the inhibition process. The inhibition data presented in this study demonstrate that heptosyltransferase WaaC is the second enzyme ever reported for which significant levels of multivalent inhibition have been measured.…”
Section: Inhibition Of Waacmentioning
confidence: 94%
“…[9] Specifically, multivalent effects have been observed with isomaltase of bakers yeast and a-mannosidase of Jack bean with K i values improved by two and three orders of magnitude, respectively, over the corresponding monomeric iminosugar. This first evidence of dramatic multivalent effects in glycosidase inhibition not only opens a new field of research, but also reveals that the multivalent approach may be an appealing tool for innovative drug discoveries.…”
Section: Introductionmentioning
confidence: 97%
“…[70][71][72] For example, the inhibition profile of fullerene hexakis-adduct 54, decorated with 12 iminosugar residues, was systematically evaluated towards various glycosidases. [70] Remarkably, significant multivalent effects were evidenced for the first time.…”
Section: Fullerene Sugar Ballsmentioning
confidence: 99%